KINSHASA PUPILS' ATTITUDE TO EDUCATIONAL VIOLENCE - Eustache BANZA NSOMWE -; Jonathan ENGUTA MWENZI (Universitaria Publishing House, Craiova, 2023)
The aim of this study was to assess the attitudes of secondary school pupils in Kinshasa towards educational violence. In addition, it had the specific aim of studying the effects of sociodemographic variables on pupils' attitudes to such violence. To this end, a scale of attitudes to educational violence was administered to a sample of 309 secondary school pupils from three Kinshasa schools (Institut Technique et Pédagogique Mokengeli, Complexe Scolaire Cardinal Mosengwo and Complexe Scolaire les Bâtisseurs). The results revealed that 278 pupils (89.9%) had been victims of educational violence during their school career. The results also revealed a trend towards the normalization of acts of physical violence. However, acts of verbal and psychological violence were not tolerated by the subjects surveyed. In the face of such acts, respondents resort to passive attitudes (sadness, resignation, indifference and a sense of injustice). Two of the five variables in the study influenced subjects' attitudes to educational violence (school and experience of educational violence).